A Bibliometric Analysis of Ecotourism Development for Sustainable Tourism - Haryanto, Eko; Makiya, Kiki Rizki; Noviati, Fitria (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
Sustainable tourism development is a widely applied concept in various regions, both in Indonesia and abroad. Ecotourism, in particular, is a form of tourism activity that ensures the implementation of sustainable tourism. The theme of ecotourism has been extensively researched in various countries. Ecotourism has become a significant research theme over the last two decades, yielding critical results on environmental and natural conditions.Purpose: This study aims to examine research in the field of ecotourism and sustainable tourism from 2018 to 2023.Research methods: Using Publish or Perish (PoP) software to gather data from the Google Scholar database, specifically focusing on journal articles with the keywords